Legal Certainty and Public Trust in the Legal System: A Qualitative Analysis - Harun Pandia (AKADEMI TEKNIK ADI KARYA, 2025)
This study examines the relationship between legal certainty and public trust in the legal system through a qualitative analytical approach grounded in Legal Studies and Sociolegal Studies. Legal certainty, understood as the clarity, consistency, and predictability of legal norms and their enforcement, is widely regarded as a fundamental principle of the rule of law. However, in many contexts, inconsistencies in legal interpretation, selective enforcement, and procedural inefficiencies have contributed to declining levels of public trust. This study aims to explore how perceptions of legal certainty influence public confidence in legal institutions and to identify key factors shaping this relationship.The research employs a qualitative design using in-depth interviews, focus group discussions, and document analysis involving community members, legal practitioners, and institutional stakeholders. Data were analyzed thematically to capture patterns related to perceptions of fairness, transparency, and accountability within the legal system. The findings reveal that higher levels of perceived legal certainty are strongly associated with increased public trust, particularly when legal processes are transparent, consistent, and accessible. Conversely, ambiguity in regulations, unequal application of the law, and lack of institutional accountability significantly undermine trust.Furthermore, the study highlights that public trust is not solely determined by formal legal frameworks but also by the lived experiences of individuals interacting with legal institutions. The research concludes that strengthening public trust requires a comprehensive approach that enhances legal clarity, institutional integrity, and participatory engagement. This study contributes to ongoing discussions on building a credible and inclusive legal system capable of ensuring justice and social stability.